Annual Plan Proposals 2004-2005 GN Statement and Its Annexures Andaman And Nicobar Administration - Planning Commission (Planning Commission, 2004)
Agriculture and Allied Activities, Rural Development, Special Areas Programmes, Irrigation and Flood Control, Energy, Industries and Minerals, Transport, Communication, Science and Technology, General Economic Services, Social Services.
Andaman and Nicobar Administration, Planning Department